Pengembangan Media Belajar E-LKPD Berbasis Game Wordwall Pada Materi Campuran Untuk Meningkatkan Literasi Sains Peserta Didik Di Kelas VIII - Lely Yanuarta; Yudha Irhasyuarna; Ellyna Hafizah (CV.ITTC INDONESIA, 2026)
Scientific literacy involves understanding scientific concepts using information to solve problems and making decisions based on scientific findings. This study will build an e-LKPD (Electronic Student Worksheet) based on the mixed wordwall game to increase eighth-graders' scientific literacy. The development model and R&D process are ADDIE (Analysis, Design, Development, Implementation, Evaluation). The implementation involved 28 SMPN 1 Alalak class VIII C students in 2024–2025. Data was collected from PISA-based scientific literacy exams, expert validation sheets, and student answer questionnaires and analyzed descriptively and qualitatively. The validation results showed an N-Gain score of 0.71 (high category), an average score of 0.92 (very valid), and a practicality score of 90%. Results suggest that Wordwall-based e-LKPD improves students' study evaluation, data understanding, and scientific phenomena explanation. The findings show that the wordwall-based e-LKPD is a effective, practical, and valid learning instrument for the Merdeka Curriculum and 21st-century education.